Direct and specific binding of cholesterol to the mitochondrial translocator protein (TSPO) using PhotoClick cholesterol analogue. (21st March 2021) - Georges, Elias; Sottas, Chantal; Li, Yuchang; Papadopoulos, Vassilios
Abstract: The translocator protein (TSPO) is a five-helix transmembrane protein localized to the outer mitochondria membrane. Radioligand binding assays and chemical crosslinking showed TSPO to be a high affinity cholesterol-binding protein. In this report, we show that TSPO in mitochondrial fractions from MA-10 mouse tumour Leydig cells can interact directly and competitively with the clickable photoreactive cholesterol analogue. PhotoClick cholesterol showed saturable photoaffinity labelling of TSPO that could be specifically immunoprecipitated with anti-TSPO antibody, following the click reaction with the fluorescent-azide probe, tetramethylrhodamine (TAMRA)-azide. Moreover, excess cholesterol reduced the photolabelling of both total mitochondrial proteins and TSPO. Together, the results of this study demonstrated direct binding of PhotoClick cholesterol to TSPO and that this interaction occurs at physiologically relevant site(s). Graphical Abstract: